Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Provinsi matera Barat dalam Pengelolaan Urusan Lingkungan Hidup - Azzahra, Nadiva Salsabilla; Anggraini, Dewi; Zetra, Aidinil (Jurnal Pembangunan Nagari, 2025)
Decentralization implementation of environmental management in West Sumatra has not yet shown the role of local government in the framework of checks and balances. The urgency of environmental management issue listed in the West Sumatra Regional Government's Flagship Program requires supervision by Regional People's Representative Council (DPRD) through program formation, program budgeting, and program implementation on three supporting programs; Waste Management Program, Hazardous Waste Control Program, and The Environmental Education, Training and Counseling Program for the Community. This research uses qualitative method with case study approach, and uses Jimly Asshiddiqie's Five Aspects of Supervision in Legislative Power. The result shows that supervisory function in the management of environmental affairs is overall going well. However, the early stages of supervision; consideration of programs determination and budgeting are not so significant. Environmental Education, Training and Counseling Program for the Community is politically less optimal than the supervision of the Waste Management Program and the Hazardous and Toxic Waste Control Program. This is because DPRD is focusing more on entrusting ‘pokir’ in these programs.